Usaba Sumbu from Karangasem: A Tradition with A Thousand Pork Offering - I Made Ari Kapela (Bali Tourism Journal, 2022)
In historical records, Babad Dalem, there is a record about Usaba Sumbu, A celebration that represents the people's gratitude for the prosperity and resilience of the Gelgel Kingdom. As part of King Dalem Waturenggong’s territory, Bungaya traditional village, which today becomes part of Karangasem regency, has carried out Usaba Sumbu activities since the 16th century, even some claimed it had been performed since the 11th century. The whole series of rituals and ceremonies on Usaba Sumbu is viewed as offerings to ask for Amertha, the elixir of life. It is expected that the lord will bless the residents of the indigenous Village prosperous and welfare life. The tradition sparks a sense of togetherness and increases tolerance and cooperation among the people since the entire village community attends the annual ceremony. It encompasses cultural values, brotherhood, and economic values. The tradition lives as a cultural identity of the traditional village community in Karangasem and represents the people’s values. For instance, the value of brotherhood can be seen when the villager shares their roasted pork with others who could not afford the meat on occasion due to economic conditions or else. The high demand for porks, chickens or other livestock when preparing the ceremony allows local businesses to flourish. It indeed indirectly improves the local economy.